Emotions as an Object of Linguistic Study (on the Material of the Russian Language): Эмоции как предмет лингвистического изучения (на материале русского языка) - Kamalova, Alla A.; Berestnev, Gennady I. (Przegląd Wschodnioeuropejski, 2019)
Emotions attract attention of specialists in various fields of knowledge. Thus, linguists delineate the methods of emotions representation in language and discourse. Analysis of scientific publications reveals certain gaps in emotions study and contradictory opinions on the subject as well. The present survey focuses on problems related to emotions study in the context of psychology and linguistics methods. As a result, we postulate absence of a common definition for emotions, absence of non-contradictory inventory of emotional states and absence of criteria for delineation of emotion and feeling concepts. The article discusses the functions of the words emotion and feeling, outlines vocabulary related to emotions in the Russian language world image, and characterizes means of emotions representation in language and discourse. The article draws attention to study of emotions in cognitive and culturological linguistic dimensions; it may be useful while compiling linguistic and psychological dictionaries of emotions.